2011
DOI: 10.1080/15433710903269149
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practice Knowledge and Utilization among Social Workers

Abstract: In this study the researchers examined the knowledge, skills, and use of Evidence-Based Practice in a sample of social workers from different practice settings. Using an electronic survey, data were collected from a group of social work practitioners (N = 200). Participants in their 30s and 40s demonstrated the most knowledge and use of Evidence-Based Practice. In addition, a high percentage of social workers reported to be knowledgeable about social work research databases; a smaller percentage actually used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…This means that: 'The potential of qualitative research to help decision and policy-making… remains largely untapped' (Veltri et al 2014: 2). Recent work has also drawn attention to practicerelated issues (Avby et al 2014), particularly the need to pay more attention to how individual practitioners can be helped to use evidence-based knowledge in their everyday work-lives (Gray et al 2015;Pope et al 2011). Avby et al (2014) found in relation to social workers, for example, that the qualitatively different ways in which they understood EBP could be and categorized as: 'fragmented', 'discursive', 'instrumental', 'multifaceted' and 'critical'.…”
Section: The Evidence-based Practice Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that: 'The potential of qualitative research to help decision and policy-making… remains largely untapped' (Veltri et al 2014: 2). Recent work has also drawn attention to practicerelated issues (Avby et al 2014), particularly the need to pay more attention to how individual practitioners can be helped to use evidence-based knowledge in their everyday work-lives (Gray et al 2015;Pope et al 2011). Avby et al (2014) found in relation to social workers, for example, that the qualitatively different ways in which they understood EBP could be and categorized as: 'fragmented', 'discursive', 'instrumental', 'multifaceted' and 'critical'.…”
Section: The Evidence-based Practice Movementmentioning
confidence: 99%
“…A further theme in interviews was that police lacked the requisite skills to evaluate interventions and critically appraise evidence (see Pope et al 2011 If evaluation emerged as a key issue, demonstrating the 'legitimacy' of evidence to a range of social actors in the organisation (as a pre-requisite of implementation) was also seen as a challenge. Once again, the codified approach taken to the development of the WWCCR Toolkit acts as a technology of control over which types and forms of research are deemed legitimate for inclusion.…”
Section: Implementing Research Evidencementioning
confidence: 99%
“…However, they have some way to go to become 'learning organisations' (Maynard, 2010), which actively encourage and engage with the continuing professional development of their employees to develop the services they provide. This inhibits the ability of social work practitioners to routinely read, appraise and implement research in their practice (Morago, 2010;Pope et al, 2011).…”
Section: Barriers To Learningmentioning
confidence: 99%
“…Survey studies suggest that a majority of social workers in countries where the evidence movement has gained a foothold support the basic idea of EBP, but that they rarely search for or apply research findings in their clinical decision-making (Bergmark and Lundström 2002;Morago 2010;Pope et al 2011;Gray et al 2013). Studies exploring attempts to implement a critical appraisal model of EBP have shown several barriers to implementation (Bellamy et al 2008;Gray et al 2012).…”
Section: Introductionmentioning
confidence: 99%